Understanding the influencing mechanism of users’ participation in live streaming shopping: A socio-technical perspective - Dong, Xueyan; Liu, Xu; Xiao, Xuan (Frontiers in Psychology, 2023)
Exploring the influencing mechanism of users’ participation in live streaming shopping is an important prerequisite for understanding how to effectively transform social business activities to business value and maintain its stable development. Based on IT affordance theory and the Stimulus-Organic-Response framework, this study constructed a theoretical model to reveal this mechanism from the overarching perspective of socio-technical, that is making visibility, media richness, guidance shopping and real-time interactivity as stimulus factors; user’ s perceived attraction and cognitive assimilation as the internal state; and live streaming purchase intention as consumers’ response. Through 223 valid survey data analysis, we find that real-time interactive and media richness positively affect attraction; visibility, guidance shopping and media richness positively affect cognitive assimilation; cognitive assimilation and attraction positively affect consumers’ purchase intention; cognitive assimilation and attraction play a partial mediating role in the influence of technical and social factors on users’ purchase intention of live streaming.